Potential of Using Nanocarbons to Stabilize Weak Soils - Jamal M. A. Alsharef; Mohd Raihan Taha; Ali Akbar Firoozi; Panbarasi Govindasamy (Applied and Environmental Soil Science)
Soil stabilization, using a variety of stabilizers, is a common method used by engineers and designers to enhance the properties of soil. The use of nanomaterials for soil stabilization is one of the most active research areas that also encompass a number of disciplines, including civil engineering and construction materials. Soils improved by nanomaterials could provide a novel, smart, and eco- and environment-friendly construction material for sustainability. In this case, carbon nanomaterials (CNMs) have become candidates for numerous applications in civil engineering. The main objective of this paper is to explore improvements in the physical properties of UKM residual soil using small amounts (0.05, 0.075, 0.1, and 0.2%) of nanocarbons, that is, carbon nanotube (multiwall carbon nanotube (MWCNTs)) and carbon nanofibers (CNFs). The parameters investigated in this study include Atterberg’s limits, optimum water content, maximum dry density, specific gravity, pH, and hydraulic conductivity. Nanocarbons increased the pH values from 3.93 to 4.16. Furthermore, the hydraulic conductivity values of the stabilized fine-grained soil samples containing MWCNTs decreased from 2.16E-09 m/s to 9.46E-10 m/s and, in the reinforcement sample by CNFs, the hydraulic conductivity value decreased to 7.44E-10 m/s. Small amount of nanocarbons (MWCNTs and CNFs) decreased the optimum moisture content, increased maximum dry density, reduced the plasticity index, and also had a significant effect on its hydraulic conductivity.